PEDAGOGICAL CHARACTERISTICS OF THE DEVELOPMENT OF PHYSICAL QUALITIES OF ADOLESCENTS - Fazilov Ilkhomjon (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, experts have different opinions on which of them should be preferred in the development of physical qualities. A group of experts has provided information such as emphasizing speed, quickness-strength qualities and coordination ability.